A comparative study of maternal and perinatal outcome in patients with and without HELLP syndrome - Sujatha, M.; Meena, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: A prospective study of feto maternal outcome in severe preeclampsia and eclampsia with and without HELLP syndrome. The aim of the study was to compare the feto maternal outcome in pregnant woman with severe preeclampsia and eclampsia with HELLP syndrome and without HELLP syndrome. Methods: 100 cases of severe preeclampsia/eclampsia with and without HELLP syndrome were analyzed in Government Tirunelveli Medical College Hospital. Maternal morbidity and mortality were compared between the two groups. Results: 83.7% of cases among HELLP group had normal maternal outcome. 11.6% maternal mortality among the HELLP syndrome group. 54.5% babies among HELLP group had abnormal perinatal outcome and 24.6% among non HELLP group. Conclusions: HELLP syndrome has a significant influence on maternal and perinatal mortality and morbidity.